An Empirical Study On Factors That Influence Value-Based Sustainability Of Non-Profit Organisations In Malaysia - Samad, Nur Hayati Ab (2023)
Non-profit organisations (NPOs) play a prominent role in realising Sustainable Development Goal (SDG) 2030 through service delivery and other aspects of sustainable development. However, it was acknowledged that NPOs face two main issues that might impair the organisations’ sustainability. First, the ongoing resource constraint issues that NPOs face worsen due to the COVID-19 crisis. Second, it was observed that NPOs emphasise less on “value-based” perspectives, whereby misalignment of interest between NPOs and stakeholders was noted. This scenario may impair organisational sustainability as value creation is hampered. Thus, addressing these two main issues, this study aims to answer the question: “What does it take for NPOs operating with limited resources to attain value-based sustainability (VBS) to achieve sustainable development?”. Due to limited resources from the government and funders, NPOs need to be more independent; hence, justifying the need to study organisation-specific factors that could influence the VBS of NPOs. Therefore, in line with the Social Resource-Based View (SRBV) and Resource Dependence Theory (RDT), this study examines the organisational factors influencing the VBS of NPOs in Malaysia. The organisational factors identified are organisational capacities, stakeholder engagement, social entrepreneurship orientation (SEO), cross-sector collaboration, and organisational fit.